Grzyby pleśniowe w obiektach budowlanych po powodziach = Moulds in housing buildings after floods - Piontek, Marlena; Bednar, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Problem of moulds in buildings is especially important in Europe and Poland territory as effect of many floods. There are performed mycological buildings partitions analysis in buildings from floods area because moulds caused biodegradation and biodeterioration of buildings materials and are harmful to people health. Mycological analysis experimented in Institute of Environmental Engineering showed that in such building are much more species of moulds than in buildings with dampness from another reasons. It is because floods water contain organic materials what caused such number of moulds as various is this material (foods, soil, wastes, cesspit, plant products, compost, dead animals, sediment from sewage treatment plant and other).
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); grzyby pleśniowe; budownictwo mieszkaniowe; powódź; moulds; housing buildings; flood